2008 49th Annual IEEE Symposium on Foundations of Computer Science 2008
DOI: 10.1109/focs.2008.72
|View full text |Cite
|
Sign up to set email alerts
|

Lower Bounds for Noisy Wireless Networks using Sampling Algorithms

Abstract: We show a tight lower bound of Ω(N log log N ) on the number of transmissions required to compute several functions (including the parity function and the majority function) in a network of N randomly placed sensors, communicating using local transmissions, and operating with power near the connectivity threshold. This result considerably simplifies and strengthens an earlier result of Dutta, Kanoria Manjunath and Radhakrishnan (SODA 08) that such networks cannot compute the parity function reliably with signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…However, no non-trivial lower bound that apply specifically to communication networks with limited transmission radius had appeared in the literature before this work. Subsequent to the initial presentation of this work [2], Dutta and Radhakrishnan [3] showed that the same lower bound of Ω(N log log N ) holds for computing a host of boolean functions including the majority function.…”
Section: Related Workmentioning
confidence: 97%
“…However, no non-trivial lower bound that apply specifically to communication networks with limited transmission radius had appeared in the literature before this work. Subsequent to the initial presentation of this work [2], Dutta and Radhakrishnan [3] showed that the same lower bound of Ω(N log log N ) holds for computing a host of boolean functions including the majority function.…”
Section: Related Workmentioning
confidence: 97%
“…Research has shown that the answer depends crucially on the computational model in question. Models studied in this context include decision trees [21,43,19,17,38], circuits [40,22,18,30,52,53], broadcast networks [23,36,20,38,25,14,15], and communication protocols [45,46,7,24]. Some computational models exhibit a surprising degree of robustness to noise, in that one can compute the correct answer with probability 99% with only a constant-factor increase in cost relative to the noise-free setting.…”
Section: Introductionmentioning
confidence: 99%
“…However, this model assumes a complete communication network and single-bit transmissions. An extension of this line of work for random planar networks was also studied [26,38,12,13]. Unlike our own model, in this model a node can receive a message from multiple neighbors in a single round.…”
Section: Related Workmentioning
confidence: 94%